2021
DOI: 10.3389/fimmu.2020.603615
|View full text |Cite
|
Sign up to set email alerts
|

Indicator Regularized Non-Negative Matrix Factorization Method-Based Drug Repurposing for COVID-19

Abstract: A novel coronavirus, named COVID-19, has become one of the most prevalent and severe infectious diseases in human history. Currently, there are only very few vaccines and therapeutic drugs against COVID-19, and their efficacies are yet to be tested. Drug repurposing aims to explore new applications of approved drugs, which can significantly reduce time and cost compared with de novo drug discovery. In this study, we built a virus-drug dataset, which included 34 viruses, 210 drugs, and 437 confirmed related vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 56 publications
0
63
0
Order By: Relevance
“…Since the outbreak of Corona Virus Disease 2019 (COVID- 19), it spreads rapidly all over the world. There is an urgent need for effective drugs to treat and alleviate the deterioration of this novel Coronavirus (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the outbreak of Corona Virus Disease 2019 (COVID- 19), it spreads rapidly all over the world. There is an urgent need for effective drugs to treat and alleviate the deterioration of this novel Coronavirus (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of COVID-19 relied on the experience of clinicians (15,16). So far, some drugs have been proved effective in relieving and improving the symptoms of novel coronavirus pneumonia (17)(18)(19)(20)(21)(22). The drugs against the Middle East respiratory syndrome coronavirus (MERS-CoV) and severe acute respiratory syndrome coronavirus (SARS-CoV), such as Lopinavir/ritonavir, have been proved to inhibit many viruses (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various laboratory and computational studies are underway in multiple fields, and to date, several vaccines have been approved to control the virus. On October 22, 2020, Remdesivir was approved by the US Food and Drug Administration (FDA) as the first official treatment for COVID-19 [26].…”
Section: Introductionmentioning
confidence: 99%
“…With the spread of the coronavirus, the importance of using this method to find effective drugs for this new and dangerous virus has doubled. For example, in 2020, based on a study by Lim et al, It was found that ribavirin, previously used to treat infectious diseases such as hepatitis, would also be effective in treating Covid-19 [15,26]. The usefulness of drug repositioning compared to traditional drug discovery methods is to optimize the time and cost of drug production and reduce the potential risks associated with drug toxicity.…”
Section: Introductionmentioning
confidence: 99%